Ответы и объяснения

  • Участник Знаний
2013-03-14T20:23:27+04:00

2x^2-5x+3       (x-1) (2x-3)           2x-3

-------------- = ------------------  = ---------------

2x^2+5x-7          (x-1) (2x+7)           2x+7

 

Разложим числитель на мн-ли :

2x^2-5x+3=0

      5+-√25-24

x=----------------

              4

       5+-1

x=----------

           4

x= 1

x= 1, 5

2x^2-5x+3= 2 (x-1) (x-1,5) = (x-1) (2x-3)

 

Разложим знаменатель на мн-ли:

2х^2+5х-7=0

      -5+-√25+ 56

x=-------------------

              4

    -5+-9

x=---------

          4

x= 1

x= -3,5

2х^2+5х-7= 2(x-1) (x+3,5)= (x-1) (2x+7)